A Potential Candidate of Lactate Dehydrogenase Inhibitor Derived from Indonesia Herbal Compounds - Adam Haviyan Nasrullah; Dono Indarto; Riza Novierta Pesik; R. AJ. Sri Wulandari (Nexus Kedokteran Translasional, 2017)
Introduction: Lactate dehydrogenase A (LDHA) is an enzyme that catalyzes pyruvate into lactate. LDHA plays an important role in promotion of cancer cells growth through increasing aerobic glycolysis. Because LDHA has a central role in energy metabolism, it become a molecular target for development of anticancer drug. This was a biocomputational study that aimed to identify Indonesian herbal compounds which became a potential candidate of LDHA inhibitor via molecular docking analysis. Methods: Samples in this study were Indonesian herbal compounds that met the following criteria: (1) Registered on Database Herbal Indonesia, (2) had three-dimensional structure, and (3) met the criteria Lipinski rule of five. Oxamate used as a ligand standard and was validated using Autodock Vina software. Herbal compounds were also docked using the same program. Docking results were visualized using PyMOL software. LDHA inhibitor candidate is determined by comparing herbal compounds and standard ligand in terms of binding energy, binding site and Lipinski criteria. Result: Oxamate interacting with LDHA had -4.26 0.06 kcal / mol binding energy and bound to six amino acid residues at Gln 99, Arg 105, Asn 137, Arg 168, His 192, and Thr 247. A lower binding energy was observed in 23 herbal compounds and these compounds bound to LDHA at least five amino acid residues like Oxamate. Herbal compounds Phaseolic Acid, Sebacic Acid, D (-) - Fructose, Suberic Acid and Pimelic Acid interacted with amino acid residues of LDHA as same as Oxamate. The other herbal compounds interacted with less or more than six amino acid residues of LDHA. Based on characteristics of five herbal compounds, Phaseolic Acid, Sebacic Acid and Suberic Acid were probably the best candidates of LDHA inhibitor. Conclusion: Phaseolic Acid, Sebacic Acid and Suberic Acid become biocomputationally the best LDHA inhibitor. Enzymatic assays are needed to investigate whether or not all these compounds can inhibit LDHA enzyme activity. Keywords : Cancer, Inhibitor LDHA, Molecular Docking, Herbal Indonesia